Advancement in understanding the role of ferroptosis in rheumatoid arthritis - Long, Li; Guo, Hongmei; Chen, Xixi; Liu, Yan; Wang, Ruyi; Zheng, Xiaomei; Huang, Xiaobo; Zhou, Qiao; Wang, Yi (Frontiers in Physiology, 2022)
Rheumatoid arthritis (RA) is a chronic, systemic disease of unknown pathogeny with inflammatory synovitis as its main manifestation, which eventually lead to joint deformity and functional loss. Ferroptosis is a non-apoptotic cell death form that is dependent on the accumulation of intracellular iron resulting in elevated reactive oxygen species (ROS) induced-lipid peroxidation. The focus of its regulatory mechanisms mainly on System Xc- and Glutathione (GSH) metabolism, glutathione peroxidase 4 (GPX4) activity regulation, and ROS generation. Recent studies have found that there is a crossover between RA and the pathogeny processes related to ferroptosis, suggesting the involvement of ferroptosis in the onset and progression of RA. This paper provides an overview of the mechanism of ferroptosis, the link between RA and ferroptosis, and the progress of ferroptosis-related targeted drugs in the treatment of RA. Moreover, it demonstrates the promise of ferroptosis modulation as a potential target for RA treatment.